A Digital Archaeology of Early Hispanic Film Culture: Film Magazines and the Male Fan Reader - Anna Torres-Cacoullos; Elizaveta Senatorova (Journal of Cultural Analytics)
As a sociologically-oriented study, this project contributes to an archaeology of cinema fandom broadly, and early Spanish fan culture specifically, by spotlighting male readers of popular film magazines. Taking as an exploratory case study reader interactivity with the magazine _Popular Film_, analysis of correspondence and published photos of readers participating in reader contests demonstrates that the magazine’s cinema fan base was composed of a strikingly large proportion of readers who were male and that these were ardent enthusiasts of celebrity consumer culture. This is a notable contradistinction to the widely-held idea of the star-struck female movie fan. Methodologically, in conducting this study we reflect on the challenges of digital approaches to historical periodical research, where particular challenges are posed when working with magazines in a non-anglophone language, and when there are few baseline studies to rely on to guide and contextualize patterns picked up through strictly macro methods. We advocate for the affordances of a mixed macro-micro approach that combines distant reading with traditional textual studies of close reading. By adopting such a hybrid framework, digital methods provide new opportunities towards reconstructing profiles of magazine readerships and to unearth evidence of male movie fans in Spain.